Optimal contract currencies and exchange rate policy - Peter Ejler Storgaard (Danmarks Nationalbank, 2002)
The paper develops a simple stochastic new open macroeconomic model in which pricesetting firms' choice between producer currency pricing and local currency pricing is endogenous. We show that, in equilibrium, firms will denominate their export price contracts in the currency of the country with the lowest level of monetary variability. A welfare maximising government's choice of exchange rate regime is also analysed, and we find that a fixed exchange rate is preferable if the domestic monetary variability is higher than the foreign one.
Keywords: F3; F4; 330; new open-economy macroeconomics; producer currency pricing; local currency pricing; endogenous contract currencies; optimal exchange rate regime; Wechselkurspolitik; Preisrigidität; Offene Volkswirtschaft; Anpassungskosten; Duopol; Theorie